2004
DOI: 10.1074/jbc.m407012200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Interaction between the Secretory Na+-K+-Cl- Cotransporter and the Chaperone hsp90

Abstract: The first isoform of the Na ؉ -K ؉ -Cl ؊ cotransporter (NKCC1) is of central importance for the control of cellular ion concentration and epithelium-mediated salt secretion. Several studies have established that a change in intracellular [Cl ؊ ] (Cl ؊ i ) represents a key signaling mechanism by which NKCC1-induced Cl ؊ movement is autoregulated and by which Cl ؊ entry and exit on opposite sides of polarized cells are coordinated. Although this signaling mechanism is coupled to a pathway that leads to post-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
0
13
1
Order By: Relevance
“…Previous studies implicate posttranslational phosphorylation associated with NKCC1 expression changes (1,9,23,25,29,44,50). In contrast, the present investigation is the first report that ALD exerts its effects on NKCC1 expression via prevention of posttranslational ubiquitination, e.g., reduces proteasome-dependent degradation of the NKCC1 protein.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Previous studies implicate posttranslational phosphorylation associated with NKCC1 expression changes (1,9,23,25,29,44,50). In contrast, the present investigation is the first report that ALD exerts its effects on NKCC1 expression via prevention of posttranslational ubiquitination, e.g., reduces proteasome-dependent degradation of the NKCC1 protein.…”
Section: Discussioncontrasting
confidence: 50%
“…Mutation of this domain induces a kidney disease called Liddle's syndrome. Since NKCC1 and NCCs belong to the cation Cl Ϫ cotransporters (CCCs), and the CCCs exhibit a common structure in their functional regulation domains, such as the membrane associated domain and the phosphoacceptor sites (42,50), we hypothesize that there is a similarity in the regulation of NCC and NKCC1 inductions by ALD. To test this, we found that ALD increases the phosphorylation of SGK1 and Nedd4 -2 and concomitantly there is an increased induction of NKCC1 protein expression (Fig.…”
Section: /Clmentioning
confidence: 99%
“…Such mechanisms have been reported for the basolateral isoform, NKCC1. Proteins that bind to NKCC1 include SPAK and OSR1, PP1, PP2A, CIP, and Hsp90 (12)(13)(14)(15)(16)(17). The identification of several NKCC1-binding proteins supported further the view that regulation of NKCC2 might also involve a network of protein-protein interactions.…”
Section: Cation-cl Co-transporters (Cccs)mentioning
confidence: 65%
“…This later transporter family is composed of three subfamilies with a total of seven members (37,38): one Na ϩ / Cl Ϫ cotransporter (NCC), which can be inhibited by diuretics such as hydrochlorothiazide; two NKCCs, inhibited by bumetanide and less potently by furosemide; and four Na ϩ -independent K ϩ /Cl Ϫ cotransporters (KCC), which can be specifically blocked by R(ϩ)-butylindazone (39). No effects were observed on tyrosine phosphorylation ( Fig.…”
Section: Cyclic Amp Is Downstream Of the Effect Of CLmentioning
confidence: 99%